Signal peptide peptidase (SPP) assembles with substrates and misfolded membrane proteins into distinct oligomeric complexes - Schrul, Bianca; Kapp, Katja; Sinning, Irmgard; Dobberstein, Bernhard (Biochemical journal, 2010)
SPP (signal peptide peptidase) is an aspartyl intramembrane cleaving protease, which processes a subset of signal peptides, and is linked to the quality control of ER (endoplasmic reticulum) membrane proteins. We analysed SPP interactions with signal peptides and other membrane proteins by co-immunoprecipitation assays. We found that SPP interacts specifically and tightly with a large range of newly synthesized membrane proteins, including signal peptides, preproteins and misfolded membrane proteins, but not with all co-expressed type II membrane proteins...
Das PDF ist nur von der Artikelliste des Heftes aus aufrufbar
Gesehen am 04.07.2023